Whole energy balance for 1kw steam power plant - Mohd Azri, Aris (2009)
This thesis is deals with whole energy balance for 1kW steam power plant. The steam power plant that been used for this thesis is Cussons P7690/SP. The objective of this thesis is to study and analyze the whole energy balance of the steam power plant, the efficiencies, and losses. The thesis describes the procedure of three sets of experiment to achieve the objective. Those three sets of experiments are energy balance of a plant as a whole analysis, determination of principal plant component efficiencies, and energy balance for cooling tower analysis. Detail study of each plant component had been done before those experiments run. Those study such as forms of energy, function of main component in steam power plant, energy balance, component efficiencies and psychrometry theory. Parameters involved in experiment was then be analyzed to be use for each sets of experiments. These parameters as guide for the thesis will be done according to the objective and time planning. Calculation and analysis had been done after all parameters needed for the thesis has been observed. The obtained results indicated that the energy generated by the plant and energy produced from the plant are balanced. Also, the efficiency value of main plant component such as boiler, superheater, and condenser are obtained. From the calculated result, state that energies in cooling tower of this plant are not balanced. By the end of the thesis, the successful of the project had been stated and some of recommendations had been given for future research and development.